Tipe Kepribadian dan Tahapan Komunikasi Intim pada Dewasa Awal - Rani Agias Fitri; Indri Putriani (Humaniora, 2015)
Personality aspect is an aspect that cannot be discharged in an individual. It is as same as communication aspect, which is important in a relationship, including in marriage relationship. The purpose of this study is to determine whether there is a correlation between Extrovert and Introvert personality type with intimate communication phases in early adulthood. This study belongs to the type of correlation research. In this study, the result showed that there was a positive relationship between extrovert personality type with two phases of intimate communication, namely sharing the self and becoming one. Meanwhile, there was a negative relationship between Introvert personality typet with two phases of intimate communication, namely sharing the self and becoming one.